Prediction of scour downstream of triangular labyrinth weirs - Eman Aly Elnikhely (Alexandria Engineering Journal, 2020)
Estimation and control of local scouring downstream hydraulic structures is an important aspect for designing hydraulic structures. Lack predicting of local scouring can cause endangered hydraulic structures. This study performed aseries of laboratory experiments in order to look for the scouring at the downstream of triangular labyrinth weir. The effects of four different weir apex angles on the local scour were tested. The tested angles were 90°, 75°, 60°, and 45° under varied rates of flow. A wier of linear crest ‘180°’ was also included in the test program to distinguish the rendition of the triangular labyrinth weir and to benchmark some existing formulas of local scouring downstream weirs. Consequently, a great reduction of the scour parameters was obtained. Results referred to that the best weir apex angle was found to be 60°, which produced minimum values of scour parameters downstream the triangular labyrinth weir. The formulas of others performed well compared to experimental results. Moreover linear regression formulae were also proposed.